Dampak Pariwisata Terhadap Kondisi Perubahan Sosial Masyarakat Suranadi - Abdul Latip Rosyidin; Dimas Rizky Jayakusuma; Alhikami Alhikami; Chantika Agustina; Ika Wijayanti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research aims to analyze the impact of tourism on social changes in Suranadi Village, West Lombok. The village has experienced rapid tourism development, bringing both positive and negative impacts on the community's life. Positive impacts include economic growth, job creation, and the preservation of local culture. However, tourism also causes significant negative impacts, such as changes in cultural values, decreased religious practice intensity, changes in dressing styles, increased crime rates, and environmental damage. The research method used is descriptive qualitative with a case study approach, involving observation, interviews, and documentation studies. The results show that tourism development in Suranadi Village brings significant economic benefits but also requires ongoing efforts to address social and environmental challenges. Therefore, sustainable tourism strategies involving local communities, strict supervision of tourism activities, and environmental conservation programs are needed to ensure a balance between economic benefits and the preservation of local cultural values and environment. This research provides insights for stakeholders in formulating sustainable tourism development policies and strategies in Suranadi Village.